Improving Student’s Speaking Fluency through the Implementation on Direct Interview Activity in University - Mukhlisin Mukhlisin (STAI Miftahul Ula Nganjuk, 2021)
The objectives of this research are to find out whether the use of direct interview type improves the students’ speaking skill and the strengths and weaknesses of direct interview type. The method used in the research is collaborative classroom action research. This research consisted of two cycles in which there were four steps in each cycle, namely planning, implementing, observation, and reflection. The researcher collected qualitative data of speaking test and qualitative data of classroom situation, field note, photograph, interview, and questionnaires. The results are (1) the students’ speaking skill improved the improvement of speaking score (2) direct interview type established good communication activity between the teacher and the students and improved classroom management.